CLINICAL EFFICACY OF THE VARIOUS DRUGS USED IN THE TREATMENT OF GONORRHOEA - Rehman, Shams -ur-; Khan, Amir; ullah, Aman; Akhter, Khalid (Journal of Ayub Medical College Abbottabad, 2009)
Background: Gonorrhoea is a purulent inflammation of mucus membrane of the genital tract and is a highly contagious sexually transmitted disease (STD) caused by the bacterium Neisseria gonorrhoae. Both men and women can be infected through a variety of sexual contact behaviours including vaginal, anal or oral intercourses. This comparative study was carried out in New Gulail Polyclinic Jeddah, KSA from Jan 2003 to March 2004 to find the clinical efficacy of ciprofloxacin, ceftriaxone and spectinomycin, the three commonly used drugs, in the treatment of gonorrhoea. Methods: A total number of 300 patients suffering from gonorrhoea were included in this study. They were randomly divided into 3 groups of 100 patients each. Group-A patients were given Tablet Ciprofloxacin 500 mg, Group-B patients Injection Ceftriaxone 500 mg, and Group-C patients were put on Injection Spectinomycin 2 gm, all in stat dosage. On the 5th day following the treatment, all patients were re-examined and their clinical and laboratory findings were recorded and analysed. Results: On the 5th day following treatment the Group-A (n=100) showed 9 (9%) partial response and 11 (11%) cases showed no response to Ciprofloxacin. In the Group-B (n=100), 4 (4%) patients showed partial response and 6 (6%) patients showed no response to Ceftriaxone. In Group-C, out of 100 patients, 4 (4%) cases reported with partial response and 2 (2%) patients showed no response to Spectinomycin. The efficacy of these anti-microbial agents was the same in both the genders. Conclusion: Anti-microbial susceptibility of N. gonorrrhoeae to various antibiotics is gradually decreasing. In order to ensure full cure, all gonorrhoea patients should be followed-up after a single dosage of any antibiotic. Further research should continue for newer, effective, and preferably oral medication for the treatment of gonorrhoea. Keywords: Neisseria gonorrhoeae, sexually transmitted infection, STD, Sexually Transmitted Disease, Gonorrhoea